Effect of cryogenic temperature on the strengthening mechanisms of AZ61 Mg alloy extruded at different temperatures - Hafiz Muhammad Rehan Tariq; Umer Masood Chaudry; Joung Sik Suh; Young Min Kim; Tea-Sung Jun (Journal of Materials Research and Technology)
This study investigates the influence of extrusion and deformation temperatures on the mechanical properties of the AZ61 Mg alloy. Increasing the extrusion temperature from 300 to 400 °C led to larger grain size and higher basal texture intensity. At 400 °C, the AZ61 alloy exhibited more Al–Mn phases and fewer Mg17Al12 phases, indicating enhanced dissolution of Mg17Al12 in the α-Mg matrix. Uniaxial tensile tests were conducted at room temperature (RT) and cryogenic temperature (CT, −150 °C). Despite grain growth, a higher yield strength (YS) was achieved at higher extrusion temperatures due to the texture-strengthening mechanism. However, during deformation at CT, the higher YS was primarily attributed to the formation of multiple twinning within individual grains, causing twinning interactions. These twin-interacting boundaries create additional barriers to dislocation movement. Notably, the AZ61 sample extruded at 400 °C demonstrated the formation of stacking faults during deformation at CT, with dislocations accumulating around the faults. This contributed to the best strength without compromising ductility in this sample.